Adjuvant immunotherapy improves survival in completely resected stage IB–III NSCLC: a systematic review and meta-analysis - Huang, Hong; Bao, Pengchen; Jin, Hongyu; Li, Wenyang; Shen, Hui; Qin, Zhen; Pan, Ying; Su, Xinming; Kong, Delei (Frontiers in Oncology, 2025)
BackgroundThe clinical benefits of postoperative chemotherapy for non-small cell lung cancer (NSCLC) have plateaued, thus highlighting the need for novel strategies. This meta-analysis evaluated the efficacy and safety of adjuvant immunotherapy in patients with completely resected NSCLC and wild-type epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK).MethodsPubMed, Web of Science, Embase, and the Cochrane Library were searched up to February 12, 2025, for studies assessing adjuvant immunotherapy in NSCLC. Primary endpoints included disease-free survival (DFS), overall survival (OS), correlation between subgroup characteristics and efficacy, and safety outcomes, including treatment-related adverse events (TRAEs), severe adverse events (SAEs), and treatment discontinuation.ResultsTwelve articles involving 4048 patients were included. Adjuvant immunotherapy significantly improved DFS in patients with resected stage IB–III NSCLC than supportive care or placebo (hazard ratio [HR]: 0.82, 95% confidence interval [CI]: 0.72–0.93, p = 0.01; I2 = 0%, p = 0.46). However, the OS benefit was not significant (HR: 0.9, 95% CI: 0.67–1.21, p = 0.34). DFS benefit was observed in EGFR-negative (HR: 0.75, 95% CI: 0.62–0.91, I2 = 0%), EGFR status unknown (HR: 0.78, 95% CI: 0.63–0.96, I2 = 0%), programmed cell death ligand 1 (PD-L1) 1–49% (HR: 0.75, 95% CI: 0.58–0.97, I2 = 7.13%), non-squamous cell carcinoma (HR: 0.72, 95% CI: 0.61–0.84, I2 = 0%), and never-smoking (HR: 0.68, 95% CI: 0.49–0.96, I2 = 0%) subgroups. The pooled incidences of TRAEs, SAEs, and discontinuation of treatment due to toxicity were 70% (95% CI: 62%–77%), 12% (95% CI: 8%–16%), and 17% (95% CI: 15–19%), respectively.ConclusionsAdjuvant immunotherapy improved DFS in patients with completely resected NSCLC, particularly those who were EGFR-negative, had PD-L1 levels of 1–49%, had non-squamous cell carcinoma, or never smoked.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42024547752.